Traumatic stress and accelerated DNA methylation age: A meta-analysis. (June 2018) - Wolf, Erika J.; Maniates, Hannah; Nugent, Nicole; Maihofer, Adam X.; Armstrong, Don; Ratanatharathorn, Andrew; Ashley-Koch, Allison E.; Garrett, Melanie; Kimbrel, Nathan A.; Lori, Adriana; VA Mid-Atlantic MIRECC Workgroup,; Aiello, Allison E.; et al.
Highlights: Meta-analysis suggests lifetime PTSD severity associated with advanced epigenetic age. Childhood trauma exposure also associated with advanced epigenetic age. These effects evident for Hannum but not Horvath epigenetic age algorithm. Sex and white blood cell counts also associated with advanced epigenetic age. Results highlight importance of studying health consequences of traumatic stress. Abstract: Background: Recent studies examining the association between posttraumatic stress disorder (PTSD) and accelerated aging, as defined by DNA methylation-based estimates of cellular age that exceed chronological age, have yielded mixed results. Methods: We conducted a meta-analysis of trauma exposure and PTSD diagnosis and symptom severity in association with accelerated DNA methylation age using data from 9 cohorts contributing to the Psychiatric Genomics Consortium PTSD Epigenetics Workgroup (combined N = 2186). Associations between demographic and cellular variables and accelerated DNA methylation age were also examined, as was the moderating influence of demographic variables. Results: Meta-analysis of regression coefficients from contributing cohorts revealed that childhood trauma exposure (when measured with the Childhood Trauma Questionnaire) and lifetime PTSD severity evidenced significant, albeit small, meta-analytic associations with accelerated DNA methylation age ( p s = 0.028 and 0.016, respectively). Sex, CD4T cell proportions, and natural killer cell proportions were also significantly associated with accelerated DNA methylation age (all p s < 0.02). PTSD diagnosis and lifetime trauma exposure were not associated with advanced DNA methylation age. There was no evidence of moderation of the trauma or PTSD variables by demographic factors. Conclusions: Results suggest that traumatic stress is associated with advanced epigenetic age and raise the possibility that cells integral to immune system maintenance and responsivity play a role in this. This study highlights the need for additional research into the biological mechanisms linking traumatic stress to accelerated DNA methylation age and the importance of furthering our understanding of the neurobiological and health consequences of PTSD.